Efeito da vancomicina sobre o crescimento e a virulência de células planctônicas e biofilmes de Trichosporon spp - Silva, Bruno Nascimento da (2020)
Species of the genus Trichosporon have been recognized as agents of invasive fungal infections in vulnerable individuals, such as neutropenic patients with hematological malignancies, carriers of the HIV / AIDS virus, in addition to patients undergoing treatment with chemotherapy, corticosteroids, antifungals and antibacterials. Since antibiotic therapy is an important risk factor for the appearance of IFIs, this study aimed to analyze the effect of vancomycin (VAN) against clinical strains of Trichosporon spp. The effect of the antibiotic on planktonic growth and biofilm formation of T. inkin (n = 6) and T. asahii (n = 6) was investigated. The antibiotic was tested at concentrations equivalent to the plasma peak (PP; 30 μg / ml) and half of the plasma peak (PP / 2; 15 μg / ml). Planktonic growth kinetics was assessed by means of metabolic analysis of viable cells; biofilms were formed in polystyrene microplates and analyzed for viability and biomass in four stages: during adhesion (0h), after 6 h of cell adhesion, development after 24 h of incubation and after biofilm maturation (48 h). The effect of VAN on the quantification of persistent cells within the biofilm was also verified, as well as the susceptibility of these cells to amphotericin B. The effect of VAN on the virulence of Trichosporon spp. was evaluated by the experimental infection model with the nematode Caenorhabditis elegans. Finally, the morphology and ultrastructure of biofilms were evaluated by Scanning Electron Microscope and Confocal Laser Scanning Microscopy. It was observed that VAN (PP) was able to stimulate metabolic activity in 8/12 strains grown in planktonic form and also stimulated the metabolic activity and biomass of biofilms at all times of development. The antibiotic (PP) increased the amount of persistent cells in 8/12 strains of Trichosporon spp. The persistent cells of biofilms formed with VAN showed greater tolerance to amphotericin B, when compared to persistent cells obtained from biofilms free from VAN. Tests with C. elegans showed that VAN was able to increase the virulence of Trichosporon spp., Causing nematode mortality after the 2nd day of infection. Ultrastructural analysis showed greater cellularity, biomass and greater tolerance to amphotericin B in biofilms cultivated with VAN, in comparison with control biofilms. This study showed that VAN stimulates the growth of planktonic cells and biofilms of T. inkin and T. asahii and increases fungal virulence in vivo.